Improving students' self-confidence and learning achievement through contextual teaching and learning assisted by puzzle media - Fira Nopiana; Aji Heru Muslim (STKIP Melawi, 2026)
This study was motivated by the low level of students' self-confidence and learning achievement in Pancasila Education among Grade VB students at SD Negeri 2 Dukuhwaluh. Preliminary data showed that only 26.3% of students demonstrated good self-confidence, while 42.11% of students had not yet achieved the minimum mastery criterion. This study aimed to improve both aspects through the Contextual Teaching and Learning (CTL) model assisted by puzzle media. The research employed classroom action research conducted in two cycles, involving 19 students as participants. Data were collected using observation sheets, questionnaires, and achievement tests and were analyzed using descriptive quantitative and qualitative techniques. The findings showed that students' self-confidence increased from 54.4% in Cycle I to 83% in Cycle II. Likewise, students' learning achievement improved from 63.15% in Cycle I to 89.47% in Cycle II. These results indicate that the CTL model assisted by puzzle media is effective in improving the self-confidence and learning achievement of Grade VB students at SD Negeri 2 Dukuhwaluh.